Réflexions autour des « Fronts écologiques » dans le nord de l’Alberta (Canada) - Stéphane Héritier (L'Espace Politique)
This article explores the notion of “Ecological frontier.” Created on the basis of historical and geographical research in South Africa focusing, the notion of "ecological frontier" can be "resigned" and used to present a better understanding of recent geographical processes in northern Alberta. The aim is to transfer the notion developed in a different historical context to highlight its usefulness for out understanding of how environments - deeply transformed by commoditization of resources at geographical margins - have evolved. Alberta's ecological frontier is a competitive space marked by both horizontal confrontations (conflicting human and environmental issues surrounding extraction and protection), and by vertical confrontations (land claims or legal uses made both by the private sector and Aboriginal groups). Alberta’s emerging ecological frontier presents a complex adaptive ecological-political process echoing the notion of panarchy.